Upaya Peningkatan Daya Saing Wirausaha Pemula di Kota Solok Melalui Pelatihan Manajemen Usaha - Perdana Oskar, Dimas; Jum’adil Dwi Zulstra (LPPI UMN AL WASHLIYAH, 2025)
Abstract This Community Service Program focuses on strengthening the competitiveness of novice entrepreneurs in Solok City in response to the growing number of individuals choosing entrepreneurship due to limited formal employment opportunities. Although Solok City has considerable entrepreneurial potential, the managerial capacities of novice entrepreneurs have not yet fully met the demands of an increasingly competitive market. Common challenges include weak business planning, inaccurate calculation of cost of goods sold, limited utilization of digital marketing, and unclear business strategies and target markets. The program aims to enhance entrepreneurial management capabilities through structured and practical training covering business planning, basic financial management, and technology-based marketing strategies. The implementation methods included counseling sessions, interactive discussions, and mentoring for novice entrepreneurs. Evaluation results indicate a significant improvement in participants’ competencies, with 82% of participants showing improved ability in developing business plans, 76% demonstrating better understanding of cost calculation, and 79% beginning to effectively utilize digital media for marketing purposes. In addition, approximately 85% of participants exhibited increased commitment and readiness to manage their businesses sustainably. These findings suggest that management training plays an important role in improving the competitiveness of novice entrepreneurs and supports their potential growth into sustainable and competitive local enterprises.